The Effect of Professional Competence, Work Motivation, and Work Discipline on Teacher Performance: The Mediation Role of School Culture - Diahsari Puspaningtyas; Jacobus Widiatmoko (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the influence of Professional Competence, Work Motivation and Work Discipline on Teacher Performance as well as the role of School Culture as a moderating variable. The study was conducted on teachers in the Regional Coordination Office Il of the Semarang City Education Office using a quantitative approach. The sample in this study amounted to 126 teacher, and the sampling technique used a proportional random sampling. Using multiple regression analysis, the result of this study indicate that professional competence teacher work motivation, work discipline and school culture have a significant positive effect on teacher performance. Furthermore, school culture can strengthen the influence of professional competence, work motivation, and work discipline on teacher performance. Thus, improving teacher performance can be achieved through strengthening competency, motivation, discipline and supporting a positive school culture. This research is expected to provide consideration for policymaker in improving the quality of education, especially in private school. Thus, improving teacher performance can be achieved through strengthening competency, motivation, discipline, and supporting a positive school culture. This research is expected to provide policymakers with valuable insights into improving professional competency, work motivation, and work discipline in relation to teacher performance in the school environment.